Pueblos indígenas = indigenous people (UN ECLAC SantiagoCL, 2009)
Presents a series of indicators of indigenous peoples in 13 Latin American countries, based on information gathered in the 1990 and 2000 population censuses in the region.
Keywords: DEMOGRAPHIC STATISTICS